Zrównoważony rozwój a nauki techniczne - Janikowski, Ryszard (Sustainable development and technical sciences, 2007)
This paper indicated that the primary source of unsustainability was inadequate knowledge level of cause-effects relationships that took place in environment, lack of awareness of depleted environmental resources, and the great opportunity for exploration and processing of natural resources created by the technical progress. On one hand technical science can create unsustainability, but on the other it can be a powerful tool, which enables fulfilling sustainable development goals. Sustainable tomorrow, will also be shaped by development of technical Sciences. Strategie development directions of science and technology will determinate the future shape of the world. In the future environmental technologies as a part of sustainable development strategies are going to have a leading role in development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 191-201